Chemical versus Mechanical and Chemical Venous Thromboembolism Prophylaxis in Neurocritically Ill Patients: A Cohort Study - Alshaya AI; Alyahya H; Alzoman R; Faden R; Alshaya OA; Al Sulaiman K; Alanazi F; Aldekhyl S (Dove Medical Press, 2023)
Abdulrahman I Alshaya,1- 3 Hayaa Alyahya,1 Reema Alzoman,1 Rawa Faden,1 Omar A Alshaya,1- 3 Khalid Al Sulaiman,1- 4 Faisal Alanazi,1- 3 Sara Aldekhyl2,3,5 1College of Pharmacy, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 2King Abdulaziz Medical City, National Guard Health Affairs, Riyadh, Saudi Arabia; 3King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 4Saudi Critical Care Pharmacy Research (SCAPE) Platform, Riyadh, Saudi Arabia; 5College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Abdulrahman I Alshaya, Clinical Affairs, College of Pharmacy, King Saud bin Abdulaziz University for Health Sciences, P.O. Box 3660, Riyadh, 11481, Saudi Arabia, Tel +966 11-429-9999, Fax +966 11-849-5085, Email alshayaab@gmail.comPurpose: Patients admitted with neurocritical illness are presumed to be at high risk for venous thromboembolism (VTE). The administration of chemical and/or mechanical VTE prophylaxis is a common practice in critically ill patients. Recent data did not show a significant difference in the incidence of VTE between chemical compared to a combined chemical and mechanical VTE prophylaxis in critically ill patients with limited data in neurocritically ill population. The objective of this study is to investigate the incidence of VTE between chemical alone compared to chemical and mechanical VTE prophylaxis in neurocritically ill patients.Patients and Methods: This was a retrospective cohort study at a tertiary teaching hospital. Data were obtained from electronic medical records for all patients admitted with neurocritical illness from January 1, 2016, to December 31, 2020. Patients were excluded if they did not receive VTE prophylaxis during admission or were younger than 18 YO. Major outcomes were symptomatic VTE based on clinical and radiological findings, intensive care unit (ICU) length of stay (LOS), and hospital LOS. Minor outcomes included severe or life-threatening bleeding based on GUSTO criteria, and mortality at 28-days.Results: Two hundred and twelve patients were included in this study. Patients did not have any significant differences in their baseline characteristics. The incidence of VTE was similar in the chemical only group compared to the combined VTE prophylaxis group (19/166 (11.3%) vs 7/46 (15.2%)); P = 0.49. No difference between groups in their ICU LOS 6 [3- 16.2] vs 6.5 [3- 19]; P = 0.52, nor their mortality (18/166 (10.7%) vs 3/46 (6.5%)); P = 0.38, respectively. Less bleeding events were seen in the chemical prophylaxis group compared to the combined VTE prophylaxis group (19/166 (11.3%) vs 12/46 (26.1%); P = 0.01).Conclusion: Our findings observed no difference between the administration of chemical VTE prophylaxis alone compared to the combined VTE prophylaxis strategy. More data are needed to confirm this finding with more robust methodology.Keywords: deep vein thrombosis, ICU, neurocritical care, anticoagulation